Home visiting procedures for helping families - Wasik, Barbara Hanna; Bryant, Donna M., 1951-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2001)
This text offers a comprehensive survey of the history, research and practice of home visiting. This new edition comes with information on assessment instruments, and on the personal safety of the home visitor.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Home-based family services -- United States; Electronic books